Implementasi Teknik Shaping Untuk Membentuk Kebiasaan Mencuci Tangan Pada Anak Usia Dini - Intan Intan; Endang Setianingsih (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aimed to examine the implementation of the shaping technique in developing handwashing habits among early childhood children. The study employed a quantitative approach using a quasi-experimental design with a one-group pretest–posttest method. The participants were 15 children aged 4–5 years selected through purposive sampling. Data were collected using an observation checklist that assessed children's handwashing behavior before and after the intervention. The shaping technique was implemented gradually by reinforcing behaviors that increasingly approximated the target behavior through positive reinforcement, including verbal praise and reward stickers. The intervention was conducted over four weeks. The findings indicated a significant improvement in children's handwashing habits after the implementation of the shaping technique. Children became more independent in washing their hands, consistently used soap, and followed the correct handwashing procedures. These results suggest that the shaping technique is an effective behavior modification strategy for establishing healthy hygiene habits in early childhood. The study concludes that the systematic application of shaping can support teachers and parents in promoting clean and healthy behaviors from an early age, thereby contributing to disease prevention and children's overall well-being.